Structural behavior and performance of water pipes rehabilitated with a fast-setting polyurea–urethane lining. (February 2016) - Ha, S.K.; Lee, H.K.; Kang, I.S.
Graphical abstract: Scheme of the structural behavior and performance of water pipes retrofitted with a fast-setting PUU lining. Highlights: Feasibility of the fast-setting PUU as a structural lining was assessed. The hole spanning capability of water pipe with 5 mm hole was observed as 11 MPa. Peel off failure of PUU occurred at an angular displacement capacity of 6.74°. No failure of PUU was observed at a transverse shear capacity of 25% of the diameter. The fatigue resistance of PUU in the range of 10 5 cyclic loadings was achieved. Abstract: This paper presents the structural behavior and performance of a fast-setting polyurea–urethane (PUU) lining as a structural lining material for rehabilitating water pipes. To this end, a series of experimental tests were carried out to assess the following: (1) bond strength; (2) hole and gap spanning capabilities; (3) angular displacement ability; (4) transverse shear resistance; and (5) fatigue cyclic loading resistance. First, pull-off bond tests were conducted to evaluate the bond characteristics of a fast-setting PUU lining bonded to steel specimens. Surfaces were dried to ensure adequate bond strength. Second, hole and gap spanning tests were carried out to investigate the spanning capability of the lining on the water pipes. From these tests, the hole spanning capability of water pipe with 5 mm hole was observed to be 11 MPa. Then, angular displacement and transverse shear tests on fast-setting PUU lined water pipes were also carried out to evaluate the behavior and performance in bending and shear of this material. Peel off failure of PUU occurred at an angular displacement capacity of 6.74° and no failure of PUU was observed at a transverse shear capacity of 25% of the diameter. Finally, fatigue cyclic loading test was conducted to investigate the fatigue behavior and performance of the water pipe lined with this PUU material. The fatigue resistance of PUU in the range of 10 5 cyclic loadings was achieved.